Parallel Control Method Based on the Consensus Algorithm for the Non-Isolated AC/DC Charging Module - Yixin Zhu; Tao Wang; Liansong Xiong; Gaofeng Zhang; Xin Qian (Energies, 2018)
A high-power charging station for electric vehicles usually adopts a parallel structure of multiple power modules. However, due to the parameter differences among power modules, a parallel system always has circulating current issues. This paper takes a non-isolated AC/DC charging module as the research object and proposes a current sharing control strategy for multiple power modules based on the consensus algorithm. By constructing a sparse communication network with the CAN (Controller Area Network) protocol and exchanging current information, accurate current sharing among power modules is realized. Firstly, the zero-sequence circulating current issue is analyzed through a parallel model of the three-phase rectifier, with an improved circulating current restraint strategy proposed based on the zero-sequence voltage compensation. Then, the principle of the consensus algorithm is explained, which is applied to the current sharing control of multiple power modules. Finally, the proposal is tested by the designed simulation and experimental cases. From the obtained results, it can be seen that the proposed control strategy can effectively realize accurate current sharing among multiple power modules and well restrain the zero-sequence circulating current at the input side.